(untitled) (Revista Internacional de Folkcomunicação, 2021)
The work studies the relationships established between documentary filmmakers and leader folkcommunicators, identifying if the represented relationships are the result of a dialogical ethics, in the light of the buberian philosophy and folkcommunication. The research seeks to reflect on the relationships between those who produce documentaries and those who are filmed, due to the fact that the Brazilian media represents, in a generalist way, the peripheral female and male subjects. As a methodology, the work makes use of bibliographic research and descriptive film analysis on the Brazilian documentaries Fala Tu (2003) and Aqui Favela: o rap representa (2003). The choice of films is due to the difference in the approach about the hip hoppers and for the proximity in the realization of the productions. Thus, this work sought to reflect, specifically, about the relationships (ethi cs, non-ethics) that can be identified in documentary film productions, however, the notes fit for other media that promise assertions about the historical world.